2020
DOI: 10.1016/j.heliyon.2020.e04576
|View full text |Cite
|
Sign up to set email alerts
|

Low mercury, cadmium and lead concentrations in tuna products from the eastern Pacific

Abstract: Tuna species: Skipjack ( Katsuwonus pelamis ), yellowfin ( Thunnus albacares ) and bigeye ( Thunnus obesus ) are mainly processed into canned products (loins, solid pack, flakes) either in water or oil, and pre-cooked frozen loins. The National Institute of Fisheries of Ecuador (ISO/IEC 17025 certified), which is the official control laboratory, samples and analyses production batches of companies exporting to the European Union in order to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…These included concerns about the product's susceptibility to mercury poisoning, killing of dolphins from tuna nets, overconsumption, and higher prices ( Ferdman, 2014 ). However, in an eight year study from 2009 – 2016, Ormaza-González et al. (2020) determined that although there were low levels of cadmium, lead, and mercury discovered in tuna canned in Ecuadorian canneries, all levels were well below the maximum concentrations allowed by the reported literature.…”
Section: Introductionmentioning
confidence: 88%
“…These included concerns about the product's susceptibility to mercury poisoning, killing of dolphins from tuna nets, overconsumption, and higher prices ( Ferdman, 2014 ). However, in an eight year study from 2009 – 2016, Ormaza-González et al. (2020) determined that although there were low levels of cadmium, lead, and mercury discovered in tuna canned in Ecuadorian canneries, all levels were well below the maximum concentrations allowed by the reported literature.…”
Section: Introductionmentioning
confidence: 88%
“…Ormaza-González et al . [ 63 ] reported that the highest accumulation of heavy metals, including Cd, occurred in the liver of tuna fish. However, this part was rarely consumed, indicating that its adverse effect was negligible.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the daily tolerable Cd intake per kg body weight, specified by this agent, was 0.83 g. This indicated that yellowfin tuna and swordfish caught from Pacific and Hindian Oceans were safe for consumption, as they contained a low level of Cd. Ormaza-González et al [63] reported that the highest accumulation of heavy metals, including Cd, occurred in the liver of tuna fish. However, this part was rarely consumed, indicating that its adverse effect was negligible.…”
Section: Cadmiummentioning
confidence: 99%
“…As a result, mercury concentrations vary across the environment, including air, water, soil, and living organisms [ 4 ]. The relative toxicity of mercury is determined by its chemical form, and for methylmercury being one of the most poisonous compounds causing irreversible damage to the nervous system [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human exposure to mono methylmercury (MMHg), the predominant form of mercury in fish due to biomagnification in the marine food chain, is primarily through fish intake [ 6 , 7 ]. The presence of mercury in fish can be especially dangerous for pregnant women, nursing mothers, and small children [ 4 ].…”
Section: Introductionmentioning
confidence: 99%